2019
DOI: 10.1002/pmic.201900009
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics Analysis Identifies IRSp53 and Fascin as Critical for PRV Egress and Direct Cell–Cell Transmission

Abstract: Pseudorabies virus (PRV) has been widely used as a live trans‐synaptic tracer for mapping neuronal circuits. Systematically identifying mature PRV virion proteomes and defining co‐purified host proteins are necessary to fully understand the detailed mechanism underlying PRV transmission processes. Here, a PRV virion purification strategy based on sorting with flow cytometry is developed and the mature extracellular and intracellular PRV virion proteomes using LC coupled with MS/MS are characterized. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 70 publications
6
9
0
Order By: Relevance
“…In contrast, the inverse BAR (I-BAR) domain, which is found in missing in metastasis (MIM), insulin receptor substrate p53 (IRSp53), and three other mammalian proteins, is zeppelin-shaped, and binds to the membrane through the convex surface, resulting in the opposite plasma membrane topology (Suetsugu, 2010); that is, protrusions including filopodia and dendritic spines (Kawabata Galbraith et al, 2018;Mattila et al, 2007;Millard et al, 2005;Pyk€ al€ ainen et al, 2011;Saarikangas et al, 2015Saarikangas et al, , 2009Suetsugu et al, 2006). Interestingly, some reports suggested the involvement of I-BAR proteins in virus budding, a virus particle release process, implying a potential role in the scission of cellular protrusions (Thomas et al, 2015;Yu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the inverse BAR (I-BAR) domain, which is found in missing in metastasis (MIM), insulin receptor substrate p53 (IRSp53), and three other mammalian proteins, is zeppelin-shaped, and binds to the membrane through the convex surface, resulting in the opposite plasma membrane topology (Suetsugu, 2010); that is, protrusions including filopodia and dendritic spines (Kawabata Galbraith et al, 2018;Mattila et al, 2007;Millard et al, 2005;Pyk€ al€ ainen et al, 2011;Saarikangas et al, 2015Saarikangas et al, , 2009Suetsugu et al, 2006). Interestingly, some reports suggested the involvement of I-BAR proteins in virus budding, a virus particle release process, implying a potential role in the scission of cellular protrusions (Thomas et al, 2015;Yu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, actin-bundling activity of Fascin1 has been proven to facilitate release and cell-to-cell transmission of human T-cell leukemia virus type 1 (HTLV1) retrovirus [32] and, more recently, pseudorabies virus (PRV) [33]. Likewise, Epstein-Barr virus (EBV)-encoded oncoprotein (lmp1) via NF-kappaB in lymphocytes induces Fascin1 to increase their invasiveness [34].…”
Section: Discussionmentioning
confidence: 99%
“…These authors also reported 48 host proteins putatively incorporated in the virion. For Bartha PRV, a previous proteome characterization performed by Yu et al (41) identified 34 viral and 25 host proteins in the extracellular virions of a Bartha-derived mutant (expressing an mRFP-labeled VP26 and an enhanced green fluorescent protein [EGFP]-labeled gM protein). In addition, a study using stable isotope labeling by amino acids in cell culture (SILAC) revealed that Bartha PRV virions incorporate less VP11/12, VP22, and pUS3 compared to WT Kaplan virions because of mutations in the UL21 gene (42).…”
mentioning
confidence: 99%